(untitled) (International Journal of Medical and Surgical Sciences, 2015)
The Human Anatomy is an ancient Science, which uses the human body as the main material of study. However, structural differences between individuals that make up the species are quite common in the population and always emerge as a source of reports that aim to demonstrate and clarify these differences. These structural changes are called anatomical variations and may be presented externally or internally in any of the body systems, with no functional impairment to the individual. The salivary glands are exocrine glands that secrete saliva directly into the mouth through their ducts. This secretion has the functions of keeping mucous membranes moist, cleaning teeth, lubricating, dissolving and starting the food digestion process. Most of the saliva is secreted by the major salivary glands, the parotid glands and the submandibular glands, the latter being the focus of this case report. The purpose of this paper is to report a case of finding an accessory submandibular gland on a cadaver from the Human Anatomy Laboratory of the University Center of Rio Grande do Norte located in Natal, Rio Grande do Norte, Brazil. The discovery was made during a dissection of an adult male body in 2012, where an accessory submandibular gland was found in the right antimere. Thus, by identifying such variations, its clinical importance can be observed for the purpose of diagnostic imaging, surgery and anatomical teaching applied to clinic, given the scarcity of published reports, thus providing better understanding those working directly or indirectly on the subject.